Workshop On Strengthening Deep Learning In Mathematics For Supporting Elementary School Teachers’ Spasial Competences In Riau: A Preliminary Survey - Putra, Zetra Hainul; Alim, Jesi Alexander; Sari, Intan Kartika; Oktaviani, Cici; Melihayati, Ningrum; Fadillah, Rizki Rahmali; Anggraini, Shinta; Aljarrah, Ayman; Ahmad, Sagheer (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The Indonesian education curriculum continues to change over time. Currently, the government is focusing on strengthening deep learning, including in mathematics. This presents new challenges for teachers, especially elementary school teachers in Riau Province. Therefore, Community Service activities are needed to strengthen deep learning in mathematics and support the spatial abilities of these teachers. A total of 25 teachers in Riau Province were involved in the implementation of this community service activity. The results of the initial survey were conducted to measure teachers' perceptions of deep learning in mathematics and their spatial abilities. The results obtained were obtained that these teachers have a very good perception of deep learning in mathematics, with a score of 84, while their spatial abilities are still in the moderate category, with a score of 69.20. Therefore, this Workshop on strengthening deep learning in mathematics is needed to support the spatial abilities of elementary school teachers in Riau Province.